Sickle Cell Disease Team-Based Learning Module - Roderick Hori; Patricia Adams-Graves; Satoru Nishimoto; Russell Chesney; William Brescia (Association of American Medical Colleges, 2015)
Abstract Introduction This team-based learning (TBL) session examines biochemical, physiological, genetic, and clinical aspects of sickle cell disease (SCD) as well as the relationship between physicians and SCD patients. This TBL is meant to supplement concurrent courses in the first year of medical school and explores principles of biochemistry, genetics, and clinical medicine. The exercise connects structural defects in proteins to the mechanism of disease by covering the relationship between amino acid substitution and pathology; hemoglobin protein structure; protein solubility; molecular and protein diagnostic tests, vascular transit time, and oxygenation; therapeutic intervention with hydroxyurea; and the role of hemoglobin concentration on pathogenesis. The exercise also covers basic genetics and genetic counseling, family history and health counseling, exercise counseling, pain management, and selected medication management. Methods This TBL session includes a readiness assurance test (RAT) that is taken individually (iRAT) and in teams (tRAT) as well as an application that applies basic knowledge to clinical decisions. Students prepare in advance of this meeting by reading the specifically assigned portions from the article "Sickle Cell Anemia, the First Molecular Disease: Overview of Molecular Etiology, Pathophysiology, and Therapeutic Approaches," by Martin H. Steinberg, and reviewing basic protein chemistry and hemoglobin function. Results Results of the sickle cell TBL are as follows: iRAT: 73.1% (students with excused absences or malfunction of audience response systems devices were given the class mean iRAT score), tRAT: 99.6%, combined: 93.0%, and all TBL: 93.0%. Discussion The TBL has proven to be a flexible active learning experience for M1 students in the "Molecular Basis of Normal Body Function" course and an effective way to incorporate clinicians to reinforce the basic science concepts.